Implementation Of Withdrawal Of Retribution Based On Kudus Regency Regulation No. 14 Of 2012 On The Market Services Retribution In Kliwon Market Kudus - Muhammad Yanuar Ilham; Amin Purnawan (Jurnal Daulat Hukum, 2019)
Retribution is one source of local revenue. Levies are local taxes as payment for assistance.Regional service or certain special permits provided and/or supplied by Regional government for the benefit of personal or body. Retribution is very important to support local revenues, but in practice many factors that make the income retribution is less than optimal. Based on this it will be explained the problem in this research is the function of retribution, implementation and obstacles that occur in Kudus Regency Regulation No. 14 of 2012 on The Market Services Retribution In Kliwon Market Kudus. The method used in this research is empirical juridical approach, the research in the form of empirical studies to find theories about the process and about the workings of law in society. Data on the study was obtained through interviews with the Department of Trade and Traders in Kliwon Market Kudus. The results showed the actions taken by the government in addressing the factors that become obstacles in the collection of the retribution is to replace the system of retribution withdrawal which was initially carried out every day to every 30 days on the new law and issued a new policy that retribution withdrawal using E-Retribution. The government should make efforts to the training of personnel and development of merchant towing charges in the Kliwon Market Kudus. So that the withdrawal of the retribution more smoothly and does not disturb the optimization of revenue. Keywords: Implementation of Region Regulation; Market Retribution; Kudus Regency.